STRATEGI PENGEMBANGAN PARIWISATA KREATIF BAHARI DAN ANALISIS DYA SAIANG DESTINASI KEPULAUAN BANGKA BELITUNG - Malinda; Letari, Zakia Ayu (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
This study aims to analyse the development strategy for marine-based creative tourism products in the Bangka Belitung Islands and to assess the destination's feasibility and competitiveness. Bangka Belitung has significant potential for marine tourism, yet integration with the creative economy remains suboptimal. The research method employed is a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The analysis techniques include SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and 4A component analysis (Attraction, Accessibility, Amenity, Ancillary). The results indicate that Bangka Belitung is highly competitive in natural attractions but requires improvement in amenities and in creative product packaging. The recommended strategy involves strengthening local community-based creative industries and improving digital infrastructure to enhance destination competitiveness. This synergy is expected to transform the mining-based economy into a sustainable tourism economy.